Ekomisiologi integral: Dialektika teologis mandat penciptaan dengan amanat agung Kristus dalam Markus 16:15 - Pandensolang, Welly; Agatha, Krista (KURIOS, 2026)
This article examines the theological relationship between the Creation Mandate (Gen. 1:28) and the Great Commission of Christ in Mark 16:15 through the lens of integral ecomissiology. Employing a biblical-theological method combined with hermeneutical and ecological analysis, this study argues that the phrase "all creation" (πᾶσα ἡ κτίσις) in Mark 16:15 encompasses not only humanity but the entire created order, opening a comprehensive theological framework that bridges ecological responsibility and evangelistic mission. The research identifies a significant gap in missiological literature, wherein the creation mandate and the Great Commission are frequently treated as separate theological themes rather than as an integrated whole. Through exegetical analysis, intertextual dialogue, and engagement with contemporary ecotheological discourse, this article demonstrates that integral ecomissiology offers a coherent response to both the ecological crisis and the Church's missional calling. The findings suggest that faithful mission in the Anthropocene demands a holistic posture that takes the flourishing of all creation seriously as an intrinsic dimension of the proclamation of the Kingdom of God.   Abstrak Artikel ini mengkaji relasi teologis antara Mandat Penciptaan (Kej. 1:28) dan Amanat Agung Kristus dalam Markus 16:15 melalui perspektif ekomisiologi integral. Dengan menerapkan metode teologi biblika yang dikombinasikan dengan analisis hermeneutis dan ekologis, studi ini berargumen bahwa frasa "segala makhluk" (πᾶσα ἡ κτίσις) dalam Markus 16:15 mencakup bukan hanya umat manusia, melainkan seluruh ciptaan, sehingga membuka kerangka teologis yang komprehensif dalam menjembatani tanggung jawab ekologis dan misi evangelistik. Penelitian ini mengidentifikasi kesenjangan signifikan dalam literatur misiologi, di mana mandat penciptaan dan Amanat Agung sering diperlakukan sebagai tema teologis yang terpisah, bukan sebagai suatu kesatuan integratif. Melalui analisis eksegetis, dialog intertekstual, dan keterlibatan dengan wacana ekoteologi kontemporer, artikel ini mendemonstrasikan bahwa ekomisiologi integral menawarkan respons yang koheren terhadap krisis ekologis sekaligus panggilan misioner gereja. Temuan menunjukkan bahwa misi yang setia di era Antroposen menuntut sikap holistik yang memandang kesejahteraan seluruh ciptaan sebagai dimensi intrinsik dari pemberitaan Kerajaan Allah.